2018
DOI: 10.1097/md.0000000000009670
|View full text |Cite
|
Sign up to set email alerts
|

Daily 10 mg rivaroxaban as a therapy for ventricular thrombus related to left ventricular non-compaction cardiomyopathy

Abstract: Supplemental Digital Content is available in the text

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0
4

Year Published

2018
2018
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(11 citation statements)
references
References 17 publications
0
7
0
4
Order By: Relevance
“…To date, NOACs are not licensed for the treatment of LV thrombus; however, there are a growing number of recently published case studies where their use in the presence of an LV thrombus has shown impressive results. These case studies include different pathologies including LV non-compaction, hypertrophic cardiomyopathy and Chagas disease, all of which showed no embolic complications and complete LV thrombus resolution from day 7 to 2 months after initiating the chosen NOAC ( 7 , 8 , 9 ). To our knowledge, the patient presented here demonstrates the largest LV thrombus to show complete and rapid resolution within 6 days from starting treatment with Apixaban.…”
Section: Discussionmentioning
confidence: 99%
“…To date, NOACs are not licensed for the treatment of LV thrombus; however, there are a growing number of recently published case studies where their use in the presence of an LV thrombus has shown impressive results. These case studies include different pathologies including LV non-compaction, hypertrophic cardiomyopathy and Chagas disease, all of which showed no embolic complications and complete LV thrombus resolution from day 7 to 2 months after initiating the chosen NOAC ( 7 , 8 , 9 ). To our knowledge, the patient presented here demonstrates the largest LV thrombus to show complete and rapid resolution within 6 days from starting treatment with Apixaban.…”
Section: Discussionmentioning
confidence: 99%
“…Ebenso ist Vorhofflimmern eine häufige Komorbidität bei LVNC, die unabhängig vom CHA 2 DS 2 -VAsc-Score einer konsequenten Antikoagulation bedarf. Historisch wird eine Cumarin-Therapie mit einem Ziel-INR von 2,0-3,0 empfohlen, jedoch werden auch vermehrt direkte orale Antikoagulanzien (DOAK) eingesetzt [34].…”
Section: Therapieunclassified
“…The use of factor Xa inhibitors for stroke prevention in patients with LVNC has not been studied. Recently, Sun et al [37] reported a case of a 43-year-old man with LVNC and an intraventricular thrombus who was treated with rivaroxaban, 10 mg daily, for 3 months. Follow-up evaluation revealed that the thrombus diminished, but this outcome does not support the use of this class of medication for stroke prevention in patients with LVNC.…”
Section: Stroke Preventionmentioning
confidence: 99%